2004
DOI: 10.1063/1.1815058
|View full text |Cite
|
Sign up to set email alerts
|

Controlled intensity emission from patterned porous silicon using focused proton beam irradiation

Abstract: We have fabricated light emitting porous silicon micropatterns with controlled emission intensity. This has been achieved by direct write irradiation in heavily doped p-type silicon ͑0.02 ⍀ cm͒ using a 2 MeV proton beam, focused to a spot size of 200 nm. After electrochemical etching in hydrofluoric acid, enhanced photoluminescence is observed from the irradiated regions. The intensity of light emission is proportional to the dose of the proton beam, so the PL intensity of the micropattern can be tuned and var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…It has already been shown that high energy proton beam irradiation prior to electrochemical etching can be used to fabricate precise, three-dimensional microstructures in silicon [13][14][15] and GaAs [16]. In this work, we demonstrate that energetic hydrogen or helium ions can be used to produce controlled light emission from patterned porous silicon [17][18][19]. The advantage of using high energy ions over lower energy, heavier ions used in previous studies is that the range is much deeper and damage is 2-3 orders of magnitude lower.…”
Section: Introductionmentioning
confidence: 91%
“…It has already been shown that high energy proton beam irradiation prior to electrochemical etching can be used to fabricate precise, three-dimensional microstructures in silicon [13][14][15] and GaAs [16]. In this work, we demonstrate that energetic hydrogen or helium ions can be used to produce controlled light emission from patterned porous silicon [17][18][19]. The advantage of using high energy ions over lower energy, heavier ions used in previous studies is that the range is much deeper and damage is 2-3 orders of magnitude lower.…”
Section: Introductionmentioning
confidence: 91%
“…53,54 This resulted in PL images containing several distinct colour emissions, from green to red on 4 Ω-cm p-type silicon, whereas on heavily doped P-type silicon (0.02Ω-cm), tuning of the PL intensity has been obtained by controlling the local resistivity with doses. 55 Though our interests is to extend ion irradiation studies on the multilayer structures, this paper mainly presents the preliminary work done so far on 0.02Ω-cm silicon to characterise PSi multilayer parameters, such as refractive index and thickness measurement and also on the reflection and PL measurements from DBRs and F-P filter. …”
Section: Porous Silicon Based Optical Microcavitymentioning
confidence: 99%
“…Photonic structures can also be built laterally. Lateral patterns can be produced by using the selectivity offered by different doping levels or types [184,185], or simply by masking techniques. A technique useful for large-scale processing is based on interference patterns produced by two or more incident coherent light beams.…”
Section: Passive Photonic Structuresmentioning
confidence: 99%